Mr: Preservasi Naskah Kuno : Studi Kasus Perpustakaan Pribadi Kemas Andi Syarifuddin di Kota Palembang - Saputra, Roki; Rochmiatun, Endang; Andhifani, Wahyu Rizky (BRIN, 2025)
This paper explores the preservation of ancient manuscripts in the private library of Kemas Andi Syarifuddin in Palembang. The study focuses on three key aspects: 1) the factors contributing to manuscript deterioration, 2) the owner's knowledge of ancient manuscript preservation, and 3) the preservation efforts undertaken. The research employs methods such as data collection, observation, interviews, documentation, and document analysis to gain a comprehensive understanding. Findings indicate that manuscript damage results from chemical factors like oxidation and humidity, biological factors such as mold and insects, and human-related factors like improper handling. The owner possesses substantial knowledge of preservation and has taken measures including proper storage, digitization, transliteration, and the use of traditional materials like tobacco and camphor to prevent damage. However, preservation efforts face challenges such as limited resources, inadequate understanding of modern conservation techniques, and potential natural disasters. This study offers valuable insights into manuscript preservation and serves as a reference for private and public libraries in safeguarding cultural heritage.